NEGATIVE AND POSITIVE EFFECTS OF USING AN ELECTRONIC DIGITAL SIGNATURE (American Journal of Technology and Applied Sciences, 2026)
This article analyzes the role of electronic digital signature (EDS) technology in the modern process of information exchange, as well as its legal, economic, and technical aspects. The research highlights the positive impacts of EDS, such as the acceleration of document workflow, ensuring confidentiality, and the efficiency of remote services. At the same time, negative consequences associated with the use of EDS, including the risks of cyberattacks, theft of private keys, and dependence on technical infrastructure, are systematically demonstrated. The article concludes with practical recommendations for enhancing system security.